(3cJGH ajg JbSje GdYdhe hEKHGJ GdMb hcTa Gdecfhfs - (3CHh EHQGgje ESeGYjd Hf eMeO Hf MGeO GdJejej,J (B420 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfg deG SCd ef QZH Edi GdLhGH Yf cJGH jSei JbSje GdYdhe hcTa Gdecfhf CeQfi ehdGi bGFe GdReGf hGdfhQ GdJeGe s
(3BNQgG (B:s
(3hdeG jJdi Ydjge ef Ydhe GdJhMjO Je cJGH JbSje GdYdhe hEKHGJ GdMb hcTa Gdecfhf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B37s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B378s
Keywords: (3GdJhMjO hGdedd hGdfMds